2009
DOI: 10.1093/annonc/mdp069
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab plus cisplatin–5-fluorouracil versus cisplatin–5-fluorouracil alone in first-line metastatic squamous cell carcinoma of the esophagus: a randomized phase II study of the Arbeitsgemeinschaft Internistische Onkologie

Abstract: Cetuximab can be safely combined with CF chemotherapy and may increase the efficacy of standard CF chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(180 citation statements)
references
References 26 publications
3
173
2
2
Order By: Relevance
“…It has been reported that compared with chemotherapy alone, cetuximab plus chemotherapy could more obviously improve the curative effect for metastatic SCCO (Lorenzen et al, 2009). Because the number of cases in this Meta analysis is still insufficient, conclusions were inconsistent with the previously one, it still need to continue to accumulate clinical pathological data, observe prognosis, and do a more comprehensive and further study on EGFR over-expression correlates with SCCO, so as to provide a more sufficient theoretical basis for anti-EGFR target therapy in SCCO.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that compared with chemotherapy alone, cetuximab plus chemotherapy could more obviously improve the curative effect for metastatic SCCO (Lorenzen et al, 2009). Because the number of cases in this Meta analysis is still insufficient, conclusions were inconsistent with the previously one, it still need to continue to accumulate clinical pathological data, observe prognosis, and do a more comprehensive and further study on EGFR over-expression correlates with SCCO, so as to provide a more sufficient theoretical basis for anti-EGFR target therapy in SCCO.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab combined with radiotherapy is approved for treatment of primary SCC of the oropharynx, hypopharynx, or larynx, and cetuximab combined with platinum is approved for treatment of recurrent or metastatic SCC of the oropharynx, hypopharynx, larynx, and oral cavity, based on positive clinical trials (12,13). Cetuximab has been tested in combination with irinotecan, cisplatin, and concurrent radiotherapy in esophageal cancer in multiple phase II studies (14)(15)(16)(17). The results are mixed regarding safety and question the efficacy of including cetuximab in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our own search yielded a total of 6777 records of which 45 [3][4][5] were RCTs. Of the 37 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]19,20,[22][23][24][25][26][27][28][30][31][32][33][34][36][37][38]40,41,43,45,47,48 trials of cetuximab, 32 [3][4][5][6][8][9][10][11][12][14][15][16]…”
Section: Search Strategy and Missing Trialsmentioning
confidence: 99%